A comparison of McGrath MAC, Pentax AWS, and Macintosh direct laryngoscopes for nasotracheal intubation: a randomized controlled trial - Chae YJ; Kim DH; Park EJ; Oh J; Yi IK (Dove Medical Press, 2019)
Yun Jeong Chae,* Dae Hee Kim,* Eun Jeong Park, Juyeon Oh, In Kyong Yi Department of Anesthesiology and Pain Medicine, Ajou University School of Medicine, Suwon 16499, South Korea*These authors contributed equally to this workCorrespondence: In Kyong YiDepartment of Anaesthesiology and Pain Medicine, Ajou University School of Medicine, 164 World Cup-ro, Yeongtong-gu, Suwon 16499, South KoreaTel +82 219 7522Fax +82 219 5579Email lyrin01@gmail.comPurpose: Videolaryngoscopy in nasotracheal intubation has been reported to be better than direct laryngoscopy. The most suitable type of videolaryngoscope remains unknown. This study aimed to compare two videolaryngoscopes (McGrath MAC and Pentax AWS) with a Macintosh laryngoscope during nasotracheal intubation.Methods: Overall, 123 patients older than 18 with normal airways who needed nasotracheal intubation were randomly allocated into three groups: Macintosh (n=41), McGrath (n=41), and Pentax (n=41). Intubation time was the primary outcome and subdivided into three steps: nose to oropharynx, oropharynx to laryngeal inlet, and laryngeal inlet to trachea. Time required, ease of each step, glottic view grade, modified nasal intubation–difficulty score, and subjective difficulty were evaluated.Results: Intubation time among the three groups was not significantly different (Macintosh 34.6±8.1 seconds, McGrath 35.2±7.9 seconds, Pentax 36.2±9.7 seconds; p=0.727). While the glottal view was better with videolaryngoscopes (I/IIa/IIb/III 36.6%/36.6%/19.5%/7.3% vs 82.9%/9.8%/7.3%/0%, vs 63.4%/29.3%/4.9%/2.4%, p=0.000), modified nasal intubation–difficulty score and subjective difficulty and ease of each step were not significantly different. However, the Pentax took longest for the second step (11.8±6.3 vs 10.3±3.5 vs 15.1±7.6 seconds, p=0.001) but was shortest for the third step (2.9±2.6 vs 4.4±5.6 vs 1.7±0.7 seconds, p=0.001).Conclusion: The McGrath MAC and Pentax AWS showed no benefits in intubation time or difficulty, despite better glottal views, compared to the Macintosh laryngoscope in nasotracheal intubation. Additionally, videolaryngoscopes had variable performance at different steps of nasotracheal intubation.Keywords: laryngoscopes, laryngoscopy, intubation, trachea, nose